Simulation analysis of the weekend effect's problem - Frenkel, Boris; Alberg, Dmitry; Frenkel, Ilia (Journal of Business Economics and Management, 2004)
The proposed paper uses the simulation approach to the analysis of the model, which explains the essence of the ‘Weekend Effect’ existing on the world's stock exchanges. This effect contains the difference of the daily working ratio between Saturday and Monday. The stock market is considered as the Queuing System functioning according to the Matchmaker concept.First Published Online: 14 Oct 2010